STRENGTHENING STUDENT SKILLS THROUGH TRAINING IN MAKING MEATBALLS WITH CULLED CHICKEN MEAT - Hafid, Harapin (Journal of Saintech Transfer, 2019)
Students as agents of change are required to have a lot of knowledge and skills during their studies. The addition of the ability of the skills of the students should be obtained based on practical activities during the lecture, but is often constrained by the unpreparedness of lab facilities and adequate infrastructure. This has an impact on student mastery of skills is not optimal. Application of science and technology activities aimed to establish a student majoring in animal husbandry skills through training making meatballs with chicken base material salvage. Methods are activities undertaken by: (1) lectures and discussions on potential, prospects and agribusiness agroindusti meatballs, (2) demonstration and coaching of making meatballs, (3) motivated the development of entrepreneurial spirit. The results showed that activities of the training material presented and received positive response from participants was satisfactory considering there has not yet been carried out similar activities. Generally, the participants wanted to adopt the material about making meatballs with chicken base material reject rate. Concluded that the target audience consists of students majoring in animal husbandry are very enthusiastic and active in the manufacture of technical guidance meatballs. In general, trainees wishing to do entrepreneurship by producing meatballs made ​​from chicken meat laying reject rate.